2022
DOI: 10.26855/jamc.2022.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Parameters of Rain Flow Distribution Using L-Moment Method in South Sulawesi, Indonesia

Abstract: This research is an applied research which aims to determine the type of distribution of each district/city in South Sulawesi Province. The data used are secondary data belonging to the Water Resources Management Office (PSDA) from 58 rainfall stations with a span of 31 years . The L-Moment method is a method that defines the probability density function of a distribution with its first 4 characteristics. The four characteristics are L-location πœ†πœ† 1 , L-variability πœ†πœ† 2 , L-skewness 𝜏𝜏 3 dan L-curtosis οΏ½… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Their findings revealed that among these distributions, the GEVD demonstrated superior performance. Another study conducted by Sanusi et al [11] discovered that the annual maximum rainfall data in various South Sulawesi Province districts, such as Pinrang and Takalar, was best represented by the GEVD. Susanti et al [12] concluded that the GEVD performed better than the GPA distribution for maximum rainfall data in Pekanbaru City, Riau.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that among these distributions, the GEVD demonstrated superior performance. Another study conducted by Sanusi et al [11] discovered that the annual maximum rainfall data in various South Sulawesi Province districts, such as Pinrang and Takalar, was best represented by the GEVD. Susanti et al [12] concluded that the GEVD performed better than the GPA distribution for maximum rainfall data in Pekanbaru City, Riau.…”
Section: Introductionmentioning
confidence: 99%